FROM PERCEPTION TO PRODUCTION: AN ANALYSIS OF FIRST LANGUAGE ACQUISITION IN 2.5 YEARS OLD TODDLER SPEECH - Bunga Astya Syafitri (Universitas Muhammadiyah Semarang, 2021)
This research discusses the phenomenon of first language acquisition in a 2.5 years old toddler named Rumaysaa. The role of perception and production is the key to its process. In this study, variations in children's speech in producing the word 'pantai' (beach) became the main focus to find out how the perception and production processes influence each other in providing language knowledge to the research subjects. The research method used in this research is descriptive-analytical one with a qualitative approach. This approach was chosen because it can accommodate the uniqueness shown on the speech. Several previous studies regarding first language acquisition show that children can understand the meaning even though their speech is not perfect yet or may have a bubbling accent. The result of this research showed that Rumaysaa was able to imitate the word 'pantai' (beach) which was mentioned by her mother even though it took time to get a proper understanding of phonetic sounds. It actually has proven the previous theory that says a child’s perception ability is much higher than the production ability. The imperfect speech that commonly appears for children with FLA is also found in Rumaysaa's speech. The conclusion from this research is that Rumaysaa has succeeded in perceiving the word ‘pantai’ and reproducing it through several repetitions and adjustments.